Analysis Of Strategies For Improving The Community Economy Through The Management Of The Tor Simago-Mago Tourist Village Reviewed From An Islamic Economic Perspective - Pakpahan, Mutmainnah Khoiriah; Imsar, Imsar; Silalahi, Purnama Ramadhani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to understand the strategies used to enhance the economy of the community through the management of the Tor Simago-Mago tourist village in Hutaraja Village, Sipirok District, South Tapanuli Regency, when viewed from the perspective of Islamic economics. The research method used is qualitative descriptive, with the data sources employed in this study being primary and secondary data. The data collection techniques include interviews, observations, and documentation. In this case, the researcher will interview the Head of Hutaraja Village, the Chairperson of Pokdarwis, the Manager of the Tourist Village, and several economic actors around the Tor Simago-Mago tourist attraction. The researcher will use SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to analyze the research results and then identify appropriate strategies for improving the economy of the community around Tor Simago-Mago tourism. The data analysis techniques used will be data presentation, data reduction, and drawing conclusions. Initially, the people of Hutaraja Village made a living as coffee farmers and rice farmers. It cannot be denied that since the emergence of the Tor Simago-Mago tourism site, many community members have benefited and taken advantage of it by selling goods, providing parking spaces, creating photo spots, rest areas, and so on. The position of the Tor Simago-Mago tourism in the IFE and EFE values is in Quadrant I or Strength Opportunity (SO). Therefore, the position of Tor Simago-Mago tourism is at the coordinate point (3.35; 3.02), which indicates the SO strategy, meaning that Tor Simago-Mago tourism must be bold in implementing a progressive strategy by utilizing its existing capacities and strengths to seize the opportunities it faces. One of the strategies for economic improvement that can be implemented is by empowering the existence of Tor Simago-Mago tourism, maintaining and preserving religious values in the management of Tor Simago-Mago tourism, enhancing facilities and infrastructure to provide more comfort for visitors, including places for worship, minimizing illegal levies that can disturb visitors, adding shelters for when it rains, and consistently providing good service to visitors so they are not deterred and can return at any time. Keywords: Strategy, Economy, Tourism Village, Islamic Economic Perspective